Determination and measuring some of the physical and chemical parameters in the clay of Lake Hamrin, Iraq - Jaffar, Huda Dhia (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The composition of the clay taken from the lake of Hamrin, Iraq was studied with the determination of the concentrations of the major oxides and the minor oxides in it. Kaolinite was the most dominant clay in the samples, while quartz was the most abundant non-clay mineral. Some physico-chemical parameters in lake’s water were determined such as oxygen, a chlorosity, nutrient salts, pH, total alkalinity, total nitrogen, total phosphorous and silicate. The effect of increased wastewater and human activities affected the composition of water and lead to a decrease in the productivity of the lake which was reflected by the relatively low pH values (average 8.0) and alkalinity in water as a result of the pollution. An increase in the levels of ammonia (average 5.5 IM), nitrite (average 1.6 IM) and nitrate (15IM average) were apparently due to the influence of large quantities of wastewater expelled into the lake and the utilization of ammonia by aquatic organisms with a slow assimilation. Reactive phosphate showed lower concentration in samples collected in the mid of the lake comparing with samples collecting from the shores which indicate the influence of enriched wastewater with phosphate matters